2017
DOI: 10.18291/njwls.v7i1.81403
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Mergers in Norway: Employee Health and Turnover to Three Destinations

Abstract: This article investigates the probability of turnover to three destinations following hospital mergers:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
1
5
2
1
Order By: Relevance
“…Studies of the healthcare sector have shown higher exit rates following implementation of new workflows 10 and hospital mergers across occupational groups regardless of employee health. 11 Also, higher exit rates have been found, especially among senior employees, following merger of computer companies 9 in line with other findings of higher rates of voluntary early retirement among senior employees exposed to various types of reorganisation. 8 …”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Studies of the healthcare sector have shown higher exit rates following implementation of new workflows 10 and hospital mergers across occupational groups regardless of employee health. 11 Also, higher exit rates have been found, especially among senior employees, following merger of computer companies 9 in line with other findings of higher rates of voluntary early retirement among senior employees exposed to various types of reorganisation. 8 …”
Section: Introductionsupporting
confidence: 79%
“…This study found higher retirement rates following merger, change of management and relocation at the work-unit level 8 concurrent with the present findings. Among 54 787 hospital employees in Norway, Ingelsrud 11 found a higher exit rate from the hospital sector only in the second year following hospital merger, whereas we found higher exit rates in the first year after the work-unit merger. Exposure to employee layoff and budget cut were not significantly associated with higher rates of subsequent work-unit exit.…”
Section: Discussioncontrasting
confidence: 63%
“…We assessed the sensitivity of EFW by analyzing associations between changes and company exit. These associations attenuated compared to results in table 4, but some change measures, including merger, remained significantly associated with company exit, which is contrary to previous findings (10). Not examining EFW during or before the organizational changes occurred could have underestimated the results.…”
Section: Strengths and Limitationscontrasting
confidence: 93%
“…However, there seems to be a downside to organizational changes in terms of poor employee health and well-being (1)(2)(3)(4)(5)(6). Elevated rates of employee exit (ie, turnover) from the workplace following reorganization have been reported consistently in the literature (7)(8)(9)(10)(11)(12)(13), and studies suggest that organizational changes may have a dual impact on employee exit and health (11,14). Specifically, quarterly employee-exit rates increased from 3.1% to 3.4% after implementation of new healthcare workflows (9), andrelative to no changeexcess employee-exit rates of 15-50% have been demonstrated in the years following merger, splitup, relocation, change of management, and >3 changes performed simultaneously in the healthcare sector (11,12).…”
mentioning
confidence: 99%
“…In these cases, excessive psychotropic prescription rates are found after a change in management or employee lay-off, as such changes may elevate uncertainty about future employment [ 34 ]. Hospital mergers have, also, a significant effect on long-term sickness absence of the employees in an early phase of the process and, later, from 2 to 4 years after mergers [ 33 , 60 , 61 ]. Evidence supports an association between psychosocial stress and risk of depression, anxiety, and disturbed sleep at the beginning of the merger process.…”
Section: Discussionmentioning
confidence: 99%